UNCERTAINTIES OF CLIMATE CHANGE PROJECTIONS: PRELIMINARY ANALYSIS - Santos, Thalyta Soares dos (2015)
http://dx.doi.org/10.5902/2179460X16217Although the huge scientific and computational advances of recent decades has enabled a greater understanding of the climate system and contributed to the analysis of possible causes and future impacts of global climate change, the uncertainties that pervade the climate projections, such as those reported by IPCC AR4, are still very large, particularly on a regional scale. This study evaluates the uncertainties involved in projections in South America rainfall in the the 20th and 21st century. Simulations of three climate general circulation models of the atmosphere Coupled Model Intercomparison Project 5th Phase Project (CMIP5) are evaluated according to the Reliability Ensemble Averaging (REA) method. The results of this study showed the ensemble reliability has been satisfactory for all South America in the RCP2.6 scenario, indicating good reliability of the models in this region.